Dampak Pemahaman Siswa tentang Pendidikan Agama Kristen menurut 2 Timotius 3:14-17 Terhadap Minat Belajar - Afolo Zebua; Jamli Barus; Rasmalem Raya Sembiring; Resie VM Sinaga; Genti Turnip (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Interest in learning is influenced by external factors and internal factors. Interest in learning is motivated by intelligence, learning motivation, family environment and selected friends. Students' understanding of Christian religious education according to 2 Timothy 3:14-17 includes spirituality, namely holding the truth and knowing the scriptures and with behavior in terms of guiding life and doing good. The method used is quantitative research with survey methods. The research method used is a type of quantitative research with survey methods. The research was conducted on 40 respondents. As a result, the effect of students' understanding of Christian religious education according to 2 Timothy 3:14-17 on interest in learning is significant with a correlation value of 0.627 with a good category; and the contribution is 0.393 or 39.9%, and the linear regression equation Y = 29, 18 + 0.47 X is significant. Consistently increasing the role of parents to motivate their children; increasing the teacher's role in teaching students' understanding of Christian Religious Education seriously, and being careful in choosing friends will increase interest in learning. The more students understand about Christian religious education according to 2 Timothy 3:14-17, it will have an impact on increasing student interest in learning significantly.Keywords: impact, understanding, interest of learning AbstrakMinat belajar dipengaruhi oleh faktor eksternal dan internal. Minat belajar dipengaruhi oleh kecerdasan, motivasi belajar, lingkungan keluarga dan teman. Pemahaman siswa tentang pendidikan agama Kristen menurut 2 Timotius berkaitan dengan spiritualitas, yaitu berpegang pada kebenaran dan mengetahui kitab suci dan terkait dengan perilaku yaitu membimbing hidup dan berbuat baik. Metode penelitian yang digunakan adalah jenis penelitian kuantitatif dengan metode survey. Penelitian dilakukan terhadap 40 responden. Hasil penelitian diperoleh pemahaman siswa Pendidikan Agama Kristen tentang pendidikan agama Kristen menurut 2 Timotius 3:14-17 pada minat siswa adalah signifikan dengan korelasi 0,627 dalam kategori baik, dengan kontribusi 0,393 atau 39,3% dengan persamaan regresi linier Y = 29, 18 + 0,47 X signifikan. Peningkatan peran orang tua yang secara konsisten memotivasi anaknya, peningkatan pemahaman siswa oleh guru secara serius, dan pemilihan teman yang cermat akan meningkatkan minat belajar siswa. Semakin tinggi pemahaman siswa terhadap pendidikan agama Kristen, menurut 2 Timotius 3:14-17, maka secara signifikan akan meningkatkan minat siswa terhadap Pendidikan Kristen.Kata Kunci: dampak, pemahaman, minat belajar